EFFECT OF ADDITION OF CASO4, SULPHUR, AND GRAPHITE AND TEMPERATURE VARIATIONS ON TIN VOLATILIZATION PERCENTAGE FROM TIN SMELTING SLAG BY FUMING PROCESS - Gede Ponky Aditya Ryanta, I
Tin is a metal that is very important in supporting human life because it can be used as coatings, chemicals, solder, and metal alloys. Indonesia is the second largest tin producer in the world which is 52,000 tons of production in 2015. Tin ore in Indonesia is located in Bangka Belitung and Kepulauan Riau with total reserves about 800 billion tons. Processing of tin ore in Indonesia uses two-stage smelting process. The main problem in the tin smelting process is iron which is reduced and becomes impurities in tin metal. Fuming process is one of the methods for recovering tin that has been mixed with iron. This research’s objectives are identify the effect of addition of CaSO4, sulphur, and graphite and temperature variations on tin volatilization percentage and identify the mechanism of fuming process on the first stage smelting slag from PT Timah. In this study, the amount of gypsum (CaSO4.2H2O) used was 15%, 20%, 25%, 37.5%, and 50%. The addition of 2% graphite + 20% gypsum, 4% graphite + 20% gypsum, 25% sulphur + 75% gypsum, 50% sulphur + 50% gypsum, and 75% sulphur + 25% gypsum with total sulphur base on 20% of gypsum addition. The fuming process is carried out at 1200°C for 1 hour using a muffle furnace. The fuming process is also carried out at a temperature of 1000°C, 1100°C, 1200°C, and 1300°C for 1 hour by adding 20% gypsum. Fuming results were analyzed using AAS and XRD. The results of the analysis showed that the addition of gypsum had a significant effect on the tin volatilization percentage. The optimum amount of gypsum added was 20% with a tin volatilization percentage of 81.2%. Addition of sulphur and graphite decrease the percent of tin volatilization. Temperature gives a significant effect on the addition of 20% gypsum. The optimum temperature is 1200°C with a percent of tin volatilization of 81.2%. The fuming mechanism in the addition of gypsum starts from the process of gypsum decomposition to form SO2 gas. The gas will react with SnO to form SnS. The addition of sulphur make CaO resulted from the process of gypsum decomposition form CaS. It also appears that S2 gas can turn SnO into SnS and FeO into FeS. Addition of graphite also produces CaS which can form SnS and FeS.